The Withering Effect of Raw Material on Essential Oils and its Free Menthol Content of Mentha (Mentha arvensis Linn). - Helmud P. Simanjuntak; Edy Soelistyo (Warta Industri Hasil Pertanian, 1989)
The result showed that one day storage (with wring) gave the yield of 2,28%, and free menthol content of 51.59%. It was obvious that both the yield and free menthol content obtained from one day storage are higher than those obtained from two, three and four days storage.